Penggunaan Media Pembelajaran Fisika Vascak Physics Animation untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Alat Optik Kelas XI SMA Negeri 3 Bangko Pusako - Gita Nursinta Dewi; M. Nor; Mitri Irianti (Departement of Mathematics Education, 2023)
The use of Vascak physics animation learning media aims to find out students' understanding of concepts by using Vascak physics animation learning media on optical instruments class XI SMA Negeri 3 Bangko Pusako. This type of research is a quasi-experimental design with pretest posttest, nonequivalent control group design. The research sample consisted of an experimental class and a control class which were determined randomly from homogeneous data. The data is determined through tests that are arranged based on seven indicators of understanding the concept. Data were analyzed descriptively and inferentially to find out the categories of students' conceptual understanding explanations. the results of the study show that the average understanding of students' concepts is higher than the class that applies conventional learning. This is shown in the experimental class the average percentage of students' understanding of the concept reached 77.6% and 58.4% in the control class. Thus, the use of Vascak physics animation learning media is effective in increasing students' conceptual understanding of optical instruments for class XI IPA SMA Negeri 3 Bangko Pusako.